2014
DOI: 10.3390/ijms151019018
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Preconditioning Protects against Spinal Cord Injury in Rats by Upregulating Neuronal and Astroglial Heat Shock Protein 72

Abstract: The heat shock protein 72 (HSP 72) is a universal marker of stress protein whose expression can be induced by physical exercise. Here we report that, in a localized model of spinal cord injury (SCI), exercised rats (given pre-SCI exercise) had significantly higher levels of neuronal and astroglial HSP 72, a lower functional deficit, fewer spinal cord contusions, and fewer apoptotic cells than did non-exercised rats. pSUPER plasmid expressing HSP 72 small interfering RNA (SiRNA-HSP 72) was injected into the inj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 38 publications
1
18
0
Order By: Relevance
“…It was reported that dietary restriction (Plunet et al, ), intermittent fasting (Jeong et al, ), ketogenic diet (Streijger et al, ) and exercise (Chang et al, ) improved functional recovery after contusion SCI. Interestingly, D‐β‐hydroxybutyrate (DBHB) levels were elevated during prolonged exercise, starvation or by the low carbohydrate ketogenic diet (Cotter et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that dietary restriction (Plunet et al, ), intermittent fasting (Jeong et al, ), ketogenic diet (Streijger et al, ) and exercise (Chang et al, ) improved functional recovery after contusion SCI. Interestingly, D‐β‐hydroxybutyrate (DBHB) levels were elevated during prolonged exercise, starvation or by the low carbohydrate ketogenic diet (Cotter et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, there was no difference in the expression levels of HSP70 among the three groups, although its level was increased by RS. HSP70 can suppress stress-induced myocardial apoptosis through interaction with FAF-1 35 and stress protein marker HSP 72, resulted in apoptosis suppression in exercised rats 9 . Our results suggest that chronic restraint stress can trigger stress, the lead cause of apoptosis.…”
Section: Discussionmentioning
confidence: 96%
“…Restraint stress is greater than the stress caused by forced swimming exercise 2 . Heat shock protein 72 (HSP 70), a representative marker of stress protein, can be increased by exercise 9 . Exercise can also increases the expression levels of superoxide dismutase of Mn isoform (Mn-SOD), Bax, and caspase-3 protein that inhibit apoptosis in aged rat heart 10 .…”
Section: Introductionmentioning
confidence: 99%
“…These results were replicated in a study using 6 weeks of voluntary wheel running in aged APP/PS1 mice, except decreased microgliosis was also observed (He et al, 2017). Three weeks of swimming training prior to SCI in Sprague-Dawley rats significantly increased astrocyte proliferation and expression of HSP72, a protein purported to aid in reducing neuronal and astrocytic apoptosis (Chang et al, 2014).…”
Section: Animal Models Of Astrogliosis In Other Diseasesmentioning
confidence: 73%